Identification and analysis of S-genotypes in 23 new pear cultivars - WANG Yanan; ZHANG Xiangzhan; WANG Suke; SU Yanli; WANG Long; XUE Huabai (Guoshu xuebao)
[Objective] Taxonomically, pear (Pyrus spp.) belongs to the Rosaceae family, Maloideae subfamily and Pyrus genus. It exhibits a typical gametophytic self-incompatibility (GSI) mechanism controlled by a single S-locus with multiple alleles. The S gene product within the style is a glycoprotein with ribonuclease (RNase) activity, known as S-RNase, which specifically regulates the recognition process between pollen and pistil. In commercial production, the rational configuration of pollinizer trees or the implementation of supplementary measures，like artificial pollination，is essential to ensure successful fruit set. China is endowed with a vast genetic resource of pear cultivars, comprising over 3000 varieties, which harbor a rich reservoir of S-gene alleles. Therefore, identifying the S-genotypes of pear cultivars and investigating the resources of S genes are of paramount importance for enhancing pear production and advancing genetic improvement through breeding. Recognizing the S-genotypes in new pear cultivars offers a theoretical foundation for the strategic planning of pollinizer tree arrangements and the judicious selection of hybridization parents. [Methods] DNA was extracted from the leaves of pear cultivars including Hongxiangsu, Zhongli No.1, Hongsubao, Zaohongyu, Hongmanao, Tianxin, Jinxiangyu, Danxiahong, Zhongliqiuxiang, Liuyuexiang, Hongsumi, Zhonglibiyu, Zhonglimicui, Zhongli 291, Yangguangmilu, Zaobaimi, T109, Hongyu, Hongsucui, Mantianhong, Meirensu, Zhonglijinfu, Akizuki and Kuerlexiangli pear. In this experiment, a total of three pairs of primers were designed. The first pair of primers was designed based on the primers reported. Specifically, the forward and reverse primers were selected from the highly conserved regions flanking the hypervariable region of the S gene, with high specificity. The forward primer was named FTQQYQ, with the sequence 5′-TTTACGCAGCAATATCAG-3′, and the reverse primer was named anti-IWPNV, with the sequence 5′-AC(A/G)TTCGGCCAAATAATT-3′. The second pair of primers was designed using the DANMAN software to align the resequencing data of Hongxiangsu and other samples. The forward primer was named FTQQYQ-B, with the sequence 5′-TTTAC(C/G/T)CAGCAATATCAG-3′, and the reverse primer was named anti-GIIWPN, with the sequence 5′-AC(A/G)TTCGGCCAAAT(A/T)AT-(G/T)(G/T)CC-3′. The third pair of primers was designed as specific ones for amplifying the S39-RNase gene. The forward primer was named S39-F, with the sequence 5′-TTTACTCAGCAATATCAG-3′, and the reverse primer was named S39-R, with the sequence 5′-ACGTTCGGCCAAATAATG-3′. PCR amplification was carried out for genomic DNAs of twenty-four varieties. Amplified products were separated by electrophoresis on 1.8% agarose gels, stained with ethidium-bromide (0.5%), and photographed using the Bio-Rad Gel-Doc Go documentation system. A 50 bp DNA ladder was used for estimating the molecular sizes of the amplicons. Reproducible amplified target fragments were purified using a DH101-01 DNA gel extraction kit and cloned into the pEASY-Blunt Zero Cloning Vector, and then the recombinant vectors were transformed into Escherichia coli DH5α, identified by colony PCR, and then were bidirectionally sequenced. The obtained nucleotide sequences were searched against NCBI using BLAST to identify homologous genes and compared with the available pear sequences on GenBank. The frequency of S-genes and the pollination compatibility for each cultivar were also analyzed. [Results] Utilizing the DANMAN software to align the resequencing data, new polymorphic primers FTQQYQ-B and anti-GIIWPN were redesigned. Compared to the previous primers, FTQQYQ-B and anti-GIIWPN introduced an additional 1 and 3 polymorphic sites, respectively. This enhancement allowed the new primers to amplify a more diverse range of specific S-haplotype sequences. The S-genotypes of the 23 new pear cultivars were determined as follows: Hongxiangsu S22S39; Zhongli No.1 S1S4; Hongsubao, Zaohongyu, Hongmanao, Tianxin and Jinxiangyu S3S39; Danxiahong, Zhongliqiuxiang and Liuyuexiang S4S39; Hongsumi S4S22; Zhonglibiyu S5Sd; Zhonglimicui S4S5; Zhongli291 S12S28; Yangguangmilu S12S22; Zaobaimi, T109 and Hongyu S5S12; Hongsucui, Mantianhong and Meirensu S4S12; Zhonglijinfu S5S39; Akizuki S3S4; and Kuerlexiangli pear S22S28. Statistical analysis revealed that the S4 and S39 alleles had the highest frequency among the new cultivars. The 24 pear cultivars identified in this study encompassed nine distinct S-genes, with S39 and S4 being the most frequent, each occurring in 10 out of the 48 alleles examined. The distribution of different S-genes among the tested pear cultivars was not uniform. Among the 23 new pear cultivars, 10 were found to possess the S39 genotype, indicating a relatively high proportion of the S39 genotype in the newly identified cultivars. Given that the previously identified genotype of Hongxiangsu was S22S39, specific primers for amplifying the S39 gene, namely S39-F and S39-R, were designed based on the resequencing data of Hongxiangsu. The primers S39-F and S39-R can specifically amplify the S39 genotype, providing a convenient and rapid method for the identification of the S39 genotype. Subsequently, an analysis of cross-pollination compatibility was conducted among the new cultivars. Based on the identified S-genotypes of the 23 pear varieties, it was found that the S-genotypes of Hongsubao, Zaohongyu, Hongmanao, Tianxin and Jinxiangyu were all S3S39; the S-genotypes of Danxiahong, Zhongliqiuxiang and Liuyuexiang were all S4S39; the S-genotypes of T109, Hongyu and Zaobaomi were all S5S12; and the S-genotypes of Hongsucui, Mantianhong and Meirensu were all S4S12. Since the four groups of varieties had completely identical S-genotypes, it was inferred that they cannot cross-pollinate with each other. If two varieties shared one identical S-gene, their cross-pollination may theoretically result in low fruit set or failure to bearing fruit. For example, the varieties Hongxiangsu, Hongsubao, Danxiahong, Zaohongyu, Hongmanao, Zhongliqiuxiang, Tianxin, Liuyuexiang, Jinxiangyu and Zhonglijinfu all contained the S39 gene. [Conclusion] New S-genotype specific primers FTQQYQ-B and anti-GIIWPN were designed based on the resequencing data of Hongxiangsu and other varieties, which can amplify a more diverse range of specific S-haplotype sequences. Using PCR technology combined with DNA sequencing, the S-genotypes of 23 new pear varieties were identified. Additionally, it was found that the genes S4 and S39 had the highest frequency of occurrence among the new varieties.